Change in winter climate will affect dissolved organic carbon and water fluxes in mid‐to‐high latitude catchments. Issue 5 (24th January 2013) - Laudon, Hjalmar; Tetzlaff, Doerthe; Soulsby, Chris; Carey, Sean; Seibert, Jan; Buttle, Jim; Shanley, Jamie; McDonnell, Jeffrey J.; McGuire, Kevin; Tetzlaff, Doerthe; Carey, Sean; Soulsby, Chris
Abstract There is a growing awareness that mid‐to‐high latitude regions will be strongly affected by climate change. These changes are predicted to be especially pronounced during winter, particularly at higher latitudes. To test how water quality in northern catchments could be affected by warmer winter climates, we assembled long‐term data from eight well‐studied catchments in Sweden, Scotland, Canada and the USA across a climatic gradient spanning from −2 to +9 °C in mean annual temperature and between −11.6 and + 6.1 °C in average winter temperature. We used the climatic gradient combined with inter‐annual variability among catchments to examine how warmer winters could affect the seasonality (seasonal timing) and synchroneity (coupling) of water and dissolved organic carbon (DOC) fluxes. In general, sites with colder winters (less than −5 °C) experienced an export concentrated in spring, whereas sites with warmer winters (>0 °C) displayed a more evenly distributed export across all seasons. Catchments with warmer winters also displayed less synchroneity between water and DOC flux during winter compared with colder sites, whereas the opposite was found for the spring. Patterns from the climatic gradient were supported by inter‐annual variability at individual sites where both seasonality and synchroneity in the spring were related to the temperature during the preceding winter. Our findings suggest that one likely consequence of warmer winters in northern regions is that the proportion of the annual DOC and water export will increase during winter and decrease during spring and summer. This is of importance as it is the latter seasons during which downstream utilization of both water and DOC often is largest. Copyright © 2012 John Wiley & Sons, Ltd.